2018
DOI: 10.1016/j.toxlet.2017.10.010
|View full text |Cite
|
Sign up to set email alerts
|

NOAEL-dose of a neonicotinoid pesticide, clothianidin, acutely induce anxiety-related behavior with human-audible vocalizations in male mice in a novel environment

Abstract: Neonicotinoids are novel systemic pesticides acting as agonists on the nicotinic acetylcholine receptors (nAChRs) of insects. Experimental studies have revealed that neonicotinoids pose potential risks for the nervous systems of non-target species, but the brain regions responsible for their behavioral effects remain incompletely understood. This study aimed to assess the neurobehavioral effects of clothianidin (CTD), a later neonicotinoid developed in 2001 and widely used worldwide, and to explore the target … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
58
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 65 publications
(60 citation statements)
references
References 52 publications
2
58
0
Order By: Relevance
“…However, several studies have reported the disappearance and mass death of honeybees in Europe, as well as in America and other countries, occurring since the 1990s [18,21,65], which has raised concerns about the secondary effects of these agents on non-targeted insects. It has also recently been reported that NNs have adverse effects on vertebrates for example, on the reproductive organs in reptiles [9], birds [26,60] and mammals [67], and the emotional behavior in mice [23,24,59,68]. In order to assess the risk of NNs, therefore, there is an urgent need for definitive information about their effects on mammals.…”
Section: Introductionmentioning
confidence: 99%
“…However, several studies have reported the disappearance and mass death of honeybees in Europe, as well as in America and other countries, occurring since the 1990s [18,21,65], which has raised concerns about the secondary effects of these agents on non-targeted insects. It has also recently been reported that NNs have adverse effects on vertebrates for example, on the reproductive organs in reptiles [9], birds [26,60] and mammals [67], and the emotional behavior in mice [23,24,59,68]. In order to assess the risk of NNs, therefore, there is an urgent need for definitive information about their effects on mammals.…”
Section: Introductionmentioning
confidence: 99%
“…Particularly, murine models have been used in the characterization of various effects of pesticides under controlled conditions. These comprise the evaluation of tolerance thresholds by determining the lethal dose 50 (LD 50 ) -the dose that kills 50% of the test population (Dell'Omo et al 2003;Hirano et al 2017)and adverse effects by endocrine disruption (Bhaskar and Mohanty 2014;Ghodrat et al 2014), oxidative stress (Zhao et al 2016; Morales-Prieto and Abril 2017; Latchoumycandane and Mathur 2002), genotoxic effects (Peris-Sampedro et al 2016), or neurotoxic effects (Chen et al 2016;Dell'Omo and Shore 1996;Westlake et al 1983). All these studies have involved the application of various doses of one or more (mixtures) pesticides.…”
Section: Methodsmentioning
confidence: 99%
“…Male C57BL/6N mice exposed to a single dose of noobserved-adverse-effect level (NOAEL) of clothiadin showed elevated anxiety and increase in c-fos immunoreactivity in certain brain regions (123). Imidacloprid was also reported to stimulate high-fat-dietinduced adiposity and insulin resistance in mice (124).…”
Section: Neonicotinoid Effects On Vertebratesmentioning
confidence: 99%